New Media in Medical Education - Ackerman, M. J. (Methods of Information in Medicine, 1989)
ln 1984 the American Association of Medical Colleges´ Panel on the General Professional Education of the Physician challenged the medical community to take a leadership position in the effective application of information science and computer technology to medical education. The medical education community has risen to that challenge through the use of microcomputer technology and optical disc media including the recently developed fully integrated Hypermedia environment to enhance the learning environment.
Keywords: Computer-assisted Instruction; Health Education; Microcomputers; Optical Disks; Picture Archiving and Communication